Penerapan Algoritma C4.5 Dalam Menentukan Prediksi Prestasi Siswa Pada SMPN 51 Jakarta - Muhammad Hamdan Sukri; Handrianto, Yopi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2024)
The world of education is the birthplace of state servants and the instrument for forming the personality of the state. Schools are the most important places where Indonesia's